Inhibition of 4-HYDROXYPHENYLPYRUVATE DIOXYGENASE expression by brassinosteroid reduces carotenoid accumulation in Arabidopsis. (29th October 2021) - Park, Tae-Ki; Kang, In-A; Park, Chan-Ho; Roh, Jeehee; Lee, Se-Hwa; Kim, Minjae; Jin, EonSeon; Kim, Seong-Ki; Kim, Tae-Wuk
Abstract: Unlike the indispensable function of the steroid hormone brassinosteroid (BR) in regulating plant growth and development, the metabolism of secondary metabolites regulated by BR is not well known. Here we show that BR reduces carotenoid accumulation in Arabidopsis seedlings. BR-deficient or BR-insensitive mutants accumulated higher content of carotenoids than wild-type plants, whereas BR treatment reduced carotenoid content. We demonstrated that BR transcriptionally suppresses 4-HYDROXYPHENYLPYRUVATE DIOXYGENASE ( HPPD ) expression involved in carotenogenesis via plastoquinone production. We found that the expression of HPPD displays an oscillation pattern that is expressed more strongly in dark than in light conditions. Moreover, BR appeared to inhibit HPPD expression more strongly in darkness than in light, leading to suppression of a diurnal oscillation of HPPD expression. BR-responsive transcription factor BRASSINAZOLE RESISTANT 1 (BZR1) directly bound to the promoter of HPPD, and HPPD suppression by BR was increased in the bzr1-1D gain-of-function mutation. Interestingly, dark-induced HPPD expression did not cause carotenoid accumulation, due to down-regulation of other carotenoid biosynthetic genes in the dark. Our results suggest that BR regulates different physiological responses in dark and light through inhibition of HPPD expression. Abstract : Brassinosteroid regulates carotenoid content through BZR1-mediated suppression of 4-HYDROXYPHENYLPYRUVATE DIOXYGENASE in Arabidopsis seedlings.